Pengembangan Media Video Pembelajaran Berbasis Aplikasi Canva pada Pelajaran IPAS Materi Harmoni dalam Ekosistem di Kelas V SDN 104203 Bandar Khalipah T.A. 2023/2024 - Lestari Teresia Sihaloho; Imelda Free Unita Manurung; Eva Betty Simanjuntak; Dody Feliks Pandimun Ambarita; Putra Afriadi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to develop and produce a product used as a learning medium in grade V, namely a learning video media based on the Canva application in the Science lesson Harmony in Ecosystems to improve student learning outcomes. This type of research and development (RnD) uses the ADDIE model which includes analysis, design, development, implementation, and evaluation. The instrument used is a questionnaire. The product developed must go through a validity test conducted to determine the feasibility, effectiveness and practicality before being used in learning. The feasibility test was obtained from the review of media experts obtaining a score of 90% and material experts obtained 85% in the very feasible category, the practicality of this media was obtained from the review of practitioner experts with a score of 96% in the very practical category. The effectiveness of the learning media product was obtained from the results of student tests that before using the product, 6 out of 29 students completed with a percentage of 20% completion, after using the product the percentage increased to 93% experiencing an increase of 73% with a total of 27 out of 29 students completing. This shows that the media developed is effective in improving student understanding as seen from student learning outcomes. The developed media is feasible, practical, and effective for use in the Harmony in Ecosystems learning material.